Exposure to heavy metals and red blood cell parameters in children: A systematic review of observational studies - Capitão, Carolina; Martins, Raquel; Santos, Osvaldo; Bicho, Manuel; Szigeti, Tamás; Katsonouri, Andromachi; Bocca, Beatrice; Ruggieri, Flavia; Wasowicz, Wojciech; Tolonen, Hanna; Virgolino, Ana (Frontiers in Pediatrics, 2022)
Background: Mechanistic studies show that heavy metals interfere with the hematopoietic system by inhibiting key enzymes, which could lead to anemia. However, the link between children’s exposure and red blood cell (RBC) parameters has been inconsistent. We aimed to summarize evidence on human studies exploring the association between exposure to lead, mercury, cadmium, arsenic, and chromium VI and RBC parameters in children. Methods: Following the PRISMA guidelines, we searched PubMed, Scopus, and Web of Science databases for studies published between January 2010 and April 2022. Eligible papers included human observational studies that directly assessed exposure (internal dose) to the heavy metals under study and RBC parameters in participants aged ≤18 years. We excluded studies using hospital-based samples. Study quality was assessed using the National Institutes of Health’s Quality Assessment Tools for Cohort and Cross-Sectional Studies. We synthesized the evidence using vote counting based on the direction of the relationship. Results: Out of 6 652 retrieved papers, we included a total of 38 (33 assessing lead, four mercury, two cadmium, and two arsenic; chromium VI was not assessed in any included paper). More than half of the studies were conducted in Asia. We found evidence of a positive relationship between lead concentration and hemoglobin (proportion of studies reporting negative relationships=0.750; 95% Confidence Interval (CI) 0.583, 0.874) and mean corpuscular hemoglobin (0.875; 95% CI 0.546, 0.986), and a positive relationship with red cell distribution width (0.000; 95%CI 0.000, 0.379). When considering only good-quality studies (24% of the Pb studies), only the relationship with hemoglobin levels remained (0.875; 95% CI: 0.546, 0.986). Conclusion: We found evidence of a negative relationship between lead concentration and hemoglobin and mean corpuscular hemoglobin and of a positive relationship with red cell distribution width in children. We also identified a need to conduct more studies in European countries. Future studies should use standardized practices and make efforts to increase study quality, namely by conducting comprehensive longitudinal studies. Our findings support the need to take further actions to limit heavy metal exposure during childhood.